Validitas Media Infografis Teks Editorial Melalui Swipe Tik Tok Untuk Siswa Kelas XII - Fatin, Idhoofiyatul (J-SES : Journal of Science, Education and Studies, 2024)
Students' enthusiasm for using Tik Tok social media can be utilized in learning activities, namely as a forum for using learning media. This research aims to describe the validity of editorial text infographic learning media developed using the TikTok application in swipe form. The research method used is quantitative with the research instrument in the form of a validation sheet. This media is validated by 3 validators. Based on the validation results, the media was declared suitable for use with a percentage of 79.1% on content eligibility criteria, 83.3% on language eligibility criteria, 75% on presentation eligibility criteria, 73.3% on graphic eligibility criteria, 83.3% on eligibility criteria for use.